Contextual Problem Based Learning Model to Improve Students Critical Thinking Skill in Physics Learning - Nurroniah, Novi Silvia; Irvani, Asep Irvan; Muhajir, Siti Nurdianti (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
Critical thinking skills are essential competencies in the 21st century; however, they remain low in Indonesia, particularly in physics learning. This study aims to examine the effect of a contextual problem-based learning model in enhancing the critical thinking skills of 10th-grade students on the topic of kinematics in linear motion. This model integrates problem-based learning with a contextual approach. The research employs a quantitative method with a One-Group Pretest-Posttest design. The sample consists of 35 students from a Madrasah Aliyah in Garut Regency, selected through purposive sampling. The research instruments include 12 essay questions to measure critical thinking skills, 10 questionnaire statements to assess students' responses, and an observation sheet to evaluate learning implementation. The analysis was conducted using both statistical and non-statistical methods. The statistical analysis involved comparing the mean pretest and posttest scores using IBM SPSS statistics, which showed a significant difference with a significance value of 0.001 < 0.05, where the posttest mean score (88) was higher than the pretest mean score (28). Meanwhile, the non-statistical analysis was performed by calculating the N-gain score and interpreting it using Hake’s criteria, which resulted in a score of 0.82, categorized as high. Students' responses to the contextual problem-based learning model were overwhelmingly positive, reaching 86% with a highly positive interpretation. Thus, the contextual problem-based learning model effectively enhances students' critical thinking skills, particularly in the topic of kinematics in linear motion.